Rasa syukur dan psychologycal well- being pedagang pasar tradisional - Alifa, Nur; Kamila, Aisyatin (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
This research aims to determine the relationship between gratitude and the psychological well-being of traditional market traders (Pasar Kalibaru Wetan) in Kalibaru Banyuwangi. This research uses a quantitative approach. The technique used in this research is the Simple Random Sampling technique with a sample of 134 traditional market traders who trade at the Kalibaru Wetan Market. Data collection used a scale from the Ryff psychological well-being scale with a reliability coefficient (0.920) and a gratitude scale using measuring instruments compiled from aspects of Fitzgerald (1998) and Watkins (2003) with a reliability coefficient (0.926). Based on the analysis, r=0.388, p=0.000, meaning there is a positive relationship between gratitude and psychological well-being in traditional market traders. The level of gratitude of traditional market traders will be related to their psychological well-being. To increase psychological well-being, individuals must increase their gratitude.